The Fabrication of Electronics Wearable Bracelets and approach to telecommunications: A Review - Adiprabowo , Tjahjo; Ramdani , Dani; Andriana, Andriana; Zulkarnain , Zulkarnain; Hasudungan, Olly Vertus; Ali, Erfansyah; Bethel , Ade Yoska Artadinata; Panca , Dimas (Internet of Things and Artificial Intelligence Journal, 2025)
This research aims to develop an innovative and easy-to-use fetal heart rate monitoring bracelet for pregnant women. The design of this bracelet involves various electronic aspects, including signal acquisition using optical sensors (Ultrasound Doppler, ECG, or PPG), signal processing with a microcontroller and efficient algorithms to eliminate noise and detect heart rate, as well as data display and communication via LCD screen, LED indicator, or Bluetooth connection. The power aspect is an important consideration in the selection of the right battery and power management. The design of the bracelet considers ergonomics and safety for pregnant women and fetuses. Testing and validation are carried out thoroughly, including functionality testing and clinical trials. This research also considers ethical aspects, such as data privacy and information reliability. By integrating all these aspects, it is hoped that this research can produce a prototype fetal heart rate monitoring bracelet that is accurate, safe, and comfortable to use, thus contributing to improving maternal and child health. Wearable Bracelet must-have comfort factors components consisting of Size & Dimensions, Device Weight, Strap Material, Thickness, Flexibility, Component Distribution, Edges & Corners, and Skin Ventilation. From the intructables' sample results the comfort level is 52.5%, while the tool created by Puput Dani Prasetyo has a comfort level of only 50%. And this needs to be increased to >90%.